2011
DOI: 10.1371/journal.pone.0026966
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cholesterol-Induced Post-Testicular Infertility

Abstract: This work shows that an overload of dietary cholesterol causes complete infertility in dyslipidemic male mice (the Liver X Receptor-deficient mouse model). Infertility resulted from post-testicular defects affecting the fertilizing potential of spermatozoa. Spermatozoa of cholesterol-fed lxr−/− animals were found to be dramatically less viable and motile, and highly susceptible to undergo a premature acrosome reaction. We also provide evidence, that this lipid-induced infertility is associated with the acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
(54 reference statements)
5
33
0
1
Order By: Relevance
“…This result supported with previous studies suggesting a correlation between hypercholesterolemia and histological changes in the organs [4446]. On the other hand, improvement in microscopic examination of tissues in groups fed on either oat bran or barley bran together with cholesterol.…”
Section: Discussionsupporting
confidence: 92%
“…This result supported with previous studies suggesting a correlation between hypercholesterolemia and histological changes in the organs [4446]. On the other hand, improvement in microscopic examination of tissues in groups fed on either oat bran or barley bran together with cholesterol.…”
Section: Discussionsupporting
confidence: 92%
“…This was further demonstrated after induction of the acrosome reaction, when the amount of cholesterol in control sperm was reduced by almost 50%, whereas the Dicer1 cKO sperm, which already lack an acrosome region, did not show any loss of cholesterol. Interestingly Ouvrier et al (57) also noticed increased membrane instability and immotility of sperm in a mouse model with altered lipid homeostasis in the proximal epididymis. Although these results were suggested to be caused by the accumulation of cholesteryl esters in the epididymal epithelium, the cholesterol:PUFA ratio of the sperm membrane was never measured, and the cause of infertility remained ambiguous (57).…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that lipid increment in testis from obese mouse promotes apoptosis and increment in lipid droplets in spermatogonial cells [20]. But there are no studies to describe ultrastructural sperm abnormalities that are generated as a result of increased fat supply in this particular environment.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious impact on reproductive tissues has been studied in rabbits and other species [6], [7], [10], [14][18]. Changes in lipid content in testis [19] and epididymal cells [20] were reported in normal or genetically reprogrammed animals. But few papers were focused on the addition of natural products in the food as a protective diet, in order to avoid sperm alteration [14], [15].…”
Section: Introductionmentioning
confidence: 99%